Investment in Research and Development - A Factor of Adjustment of Montenegro to the EU Economy - Marko Tomljanović; Zoran Grubišić (Journal of Central Banking Theory and Practice, 2016)
Montenegro and other Western Balkan countries are characterized by historical mortgages, political instability, commenced but uncompleted structural reforms and unfavourable economic situation, which all contributed to their lagging behind other EU member states. In addition to this, these countries have been faced with a low level of investment in research and development, unfavourable educational structure, low level of innovation and a lack of awareness about the importance of research and development in modern economies. The economic and political situation led to their determination to become a full EU member, which requires the fulfilment of specified criteria, implementation of structural reforms and "catching up" with other EU member states. Investment into research and development are found to be the key factor for fulfilling their objective – EU membership.
Keywords: F15; O32; 330; economic growth; EU; expenditure; Montenegro; research and development.